Turn-on Time Delay of Uncooled Semiconductor Laser Diode Subject to External Optical Feedback: Theoretical Analysis - Ab-Rahman, Mohammad Syuhaimi; Hassan, Mazen R (Fifth International Conference on MEMS, NANO, and Smart Systems : Dubai, UAE, 28-30 December 2009, 2009)
In this paper, the effect of external optical feedback (EOF) on the turn-on time delay (t on ) of uncooled semiconductor laser diode (SLD) is investigated theoretically. The effects temperature of operation (T) and EOF on t on are calculated according to their effect on threshold carrier density (N th ). The temperature dependence (TD) of N th is calculated according to the TD of laser cavity parameters and not by the well-known Parkove relationship. Simulation results show that t on increases as T increases due to increasing of N th . In addition, t on decreases as external reflectivity (rext) increases when the phase of reflected light is coherent. While at incoherent reflected light, ton increases sharply around specified value of r ext where this leads to inoperable case for SLD.